Characterization of Shock Wave Damages in Explosion Welded Mo/Cu Clads - Pradeep Kumar Parchuri; Shota Kotegawa; Kazuhiro Ito; Hajime Yamamoto; Akihisa Mori; Shigeru Tanaka; Kazuyuki Hokamoto (Metals, 2021)
The shock wave damage during explosive welding has not been reported in a flyer Mo plate of the Mo/Cu clads. However, it would be an inevitable problem in group VI elements. This study was aimed to characterize the shock wave damage in the Mo plate, that is less brittle than a W plate, of explosive welded Mo/Cu clads. Cladding at low horizontal collision velocities leading to high collision angles was expected to enhance the shock wave damage, and the clads resulted in less elongation in bending tests. On the other hand, in the clads obtained at high horizontal collision velocities (HCVs) with low collision angles, their bending elongation increased significantly. The shock wave damage penetrated from the surface of a Mo plate to the Mo/Cu interface, and thus reducing thickness of a Mo plate of bending specimens increased bending plastic strain. The shock wave damage is associated with kinetic energy imparted to the flyer Mo plate, and thus loss of kinetic energy due to formation of an intermediate layer at the interface and reducing thickness of a flyer Mo plate would be very helpful for decrease of shock wave damage.